223k views
0 votes
In order to solve for the variable in the equation 2 (4 x + 3) + 4 = 3 x minus (2 x + 4), Giovanni first applies the distributive property. Which equation is a result of this step? 8 x + 3 + 4 = 3 x minus 2 x + 4 8 x + 6 + 4 = 3 x minus 2 x minus 4 6 x + 5 + 4 = 3 x minus x + 3 6 x + 3 + 4 = 3 x minus x + 4

2 Answers

2 votes

Answer:

b

Explanation:

User Kim Stacks
by
5.2k points
2 votes

Answer:

B) 8x + 6 + 4 = 3x - 2x - 4

Explanation:

Just took the test on edg :)

User Tinus Wagner
by
5.3k points